1993
DOI: 10.1007/bf02996319
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma and Tumour Necrosis Factor Production in Patients withHelicobacter pylori Infection

Abstract: The production of the cytokines, interferon-gamma and tumour necrosis factor by human antral mucosa cells and stimulated peripheral blood mononuclear cells were determined by enzyme linked immunosorbent assay and L929 bioassay respectively. Tumour necrosis factor production by peripheral blood mononuclear cells in response to Helicobacter pylori stimulation was depressed in Helicobacter pylori positive individuals, compared to Helicobacter pylori negative individuals (P < 0.05). There was no difference in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 24 publications
3
13
1
Order By: Relevance
“…Production of TNF-ot and IFN--y was found to be increased in gastric mucosa in H pylorn positive individuals. 32 3 In contrast to HLA class II, we did not find an increase in CD44 expression on gastric IEL. This suggests that other factors in addition to IFN-y (possibly TNF-ot) may be needed for CD44 expression in IEL, and probably also in other cells such as gastric EP.…”
Section: Discussioncontrasting
confidence: 71%
“…Production of TNF-ot and IFN--y was found to be increased in gastric mucosa in H pylorn positive individuals. 32 3 In contrast to HLA class II, we did not find an increase in CD44 expression on gastric IEL. This suggests that other factors in addition to IFN-y (possibly TNF-ot) may be needed for CD44 expression in IEL, and probably also in other cells such as gastric EP.…”
Section: Discussioncontrasting
confidence: 71%
“…Bacterial strains also appear to be important in eliciting this response as shown by the ability of Cag-specific proteins within the Cag pathogenicity island of H. pylori to enhance NF-kB activation [Glocker et al, 1998]. In addition, H. pylori induces a potent immune response with increased production of the pro-inflammatory cytokines TNF-a and IL-1, both of which directly activate NF-kB [Crabtree et al, 1991;Fan et al, 1993]. Hence NF-kB activation in gastric epithelial cells may result from either direct contact with the bacterium or as a consequence of the immune response to the H. pylori.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Karttunen et al[107] demonstrated an increase in IFN-γ-secreting cells but not in IL-4-secreting cells in both H. pylori -positive and -negative gastric inflammation, suggesting the independence of Th1 type reaction on a pathogenetic or protective role in H. pylori -associated gastric inflammation. In the gastric explant culture from the H. pylori -positive and -negative groups, levels of IFN-γ did not differ significantly [102]. Another study demonstrated that although TNF production by antral mucosa cells in H. pylori- positive patients increased, no significant increase in IFN-γ has been shown.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…Dynamics in IL-4 or IFN-γ in gastritis were also evaluated by 6 citations [69,][71,][81, 102, 106, 107]. Agnihotri et al[106] showed an increase in IL-4 and IL-6 as well as in CD8 + lymphocytes and natural killer cells in H. pylori -associated gastric inflammation.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation